Спротив пригніченню: український досвід - Кириченко, В. Є.; Kyrychenko, V. Ye.; ORCID: http://orcid.org/0000-0002-5497-907X (Вісник Пенітенціарної асоціації України. –2019. – № 2 (8). – С. 5-16, 2019)
Досліджуються історичні витоки права на спротив пригніченню, доктринальні концепції цього права, його відображення в позитивному праві. Аналізується український досвід використання jus resistendi.

The article examines the historical roots of the right to resist oppression, the dual nature of this phenomenon as a right and as a force. The doctrinal concepts of this phenomenon, the history of its consolidation in positive law as the right to resist (jus restendi), recognition of this right as a rule of international law, pluralism of approaches to its constitutional consolidation are considered. Attention is paid to the peculiarities of jus resistendi, which are inherent, in particular, to its subject, which is characterized by multiplicity, goals, as well as to the ways of exercising this right, which cannot be fixed in positive law. Separately, the issue of the perception of this phenomenon in the Ukrainian tradition is raised. Both nonviolent forms of realization of resistance and such extreme manifestations as revolution are considered. The first attempts to consolidate this right, in national history, take place in the treaties that the princes (knyazh) concluded with their people in Kievan Rus. Further law enforcement practice was already formed in the Polish-Lithuanian Commonwealth, where any initiative of the king was perceived by the gentry as a violation of its rights and privileges and led to armed resistance. What the Polish proverb says is that «Poland exists anarchy» («Polska nierzadem stoi»). Attempts of the Ukrainian cossacks to integrate into the political society were not crowned with success. At the beginning of the struggle for rights and privileges, the cossacks used mainly peaceful, diplomatic methods of resistance, which gradually became increasingly decisive, acquiring forms of armed confrontation, which resulted in an open uprising. Further opposition of Ukrainians to oppression is associated with the Russian Empire, the most prominent manifestation of which can be considered the revolutionary events of the early twentieth century. They did not accept the oppression even after Ukraine gained independence. The right to resist oppression and tyranny has a long history, full of struggle discourses and doctrines. During the uprising, few people care about the legal side of the conflict, but when the tyrant is overthrown, there is a need to legitimize what happened. Modern Ukraine is not among the two dozen states whose main laws provide for the right of people to resist oppression. But the Ukrainian people never stopped it.

Исследуются исторические истоки права на сопротивление угнетению, доктринальные концепции этого права, его закрепление в позитивном праве. Анализируется украинский опыт использования jus resistendi.
Resistance to oppression: Ukrainian experience
Кириченко В. Є. Спротив пригніченню: український досвід / Кириченко В. Є. // Вісник Пенітенціарної асоціації України. – 2019. – № 2 (8). – С. 5-16. – DOI: https://doi.org/10.34015/2523-4552.2019.2.01.
Keywords: Держава і право. State and Law. Государство и право; Україна. Ukraine. Украина; Історія. History. История; Наукові публікації. Scientific publications. Научные публикации; право на спротив; jus resistendi; повстання; пригнічення; тиранія; деспотія; право на сопротивление; восстание; угнетение; тирания; деспотия; right to resist; insurrection; oppression; tyranny; despotism